THE INFLUENCE OF GENDER AND LANGUAGE LEARNING STRATEGY PREFERENCES TOWARDS STUDENTS’ READING COMPREHENSION - Wiwit Rosnayawati; Kaswan Kaswan (STKIP Siliwangi, 2016)
Identified as the core skill, the importance of reading is deniable for some reasons. First, reading is a receptive skill in that people get a lot of information and knowledge through reading. Second, reading is the fundamental for more advanced skill - writing. However, the performance of reading comprehension differs from one learner to others. This study investigated the influence of gender and language learning strategy (LLS) preferences towards students’ reading comprehension. The participants of this study are 155 students in 9th grade of SMP N 9 Cimahi who are divided into 68 males and 87 females. Strategy Inventory for Language Learning (SILL) proposed by Oxford (1990) and reading comprehension tests were used as the instruments. Employing causal comparative method, two way ANOVA was used in exploring 1) the differences between male and female in reading comprehension, 2) the difference between all of type LLS in reading comprehension, and 3) the interaction between gender and LLS towards reading comprehension. This study also examines what LLS most frequently used. To sum up, social strategy is the most one preferred by both male and female students. Statistically significant difference is not found both in gender (p= 0.133 > 0.05) and LLS (p=0.450 > 0.05). In addition, there is no significant difference in their interaction with regard to reading comprehension (p=0.103 > 0.05).Keywords: gender, language learning strategies (LLS), reading comprehension